Children's Career Expectations and Parents' Jobs: Intergenerational (Dis)continuities. Issue 1 (10th March 2020) - Oliveira, Íris M.; Porfeli, Erik J.; do Céu Taveira, Maria; Lee, Bora
Abstract : Children develop career expectations as they increase self‐knowledge and perceive societal affordances and barriers to life roles. Parents are powerful agents in the socialization of children to work, transmitting occupational concepts that influence children's career development. The authors used Gottfredson's (1981) and Holland's (1973) theories to test associations between children's career expectations and parents' jobs in terms of gender, prestige, and interest typology among same‐sex and cross‐sex child‐parent dyads. Data were collected from 185 Portuguese children (51.4% boys, 48.6% girls; M age = 10.41 years) from 2‐parent families. Children reported their parents' jobs and shared personal career expectations. Correlation and linear regression results indicated that fathers' male‐dominated jobs put boys at risk of gender‐based circumscription of career expectations. An intergenerational cycle of prestige inequalities was also evidenced, although parents seemed to support children's exploration of various interest areas. Future research could explore these relationships across family structures. Practice should foster children's in‐breadth career exploration and engage parents as key partners.